A-trait and risk-taking behavior in predicting injury severity among martial arts athletes - Patenteu, Ionuț; Predoiu, Radu; Makarowski, Ryszard; Predoiu, Alexandra; Piotrowski, Andrzej; Geambașu, Adina; Nica, Sarah Adriana (Frontiers in Psychology, 2023)
Introduction: Trait anxiety (A-trait) can be seen as a multiplicative function of the person-situation interaction. Considering risk-taking behavior (R-TB), literature highlights instrumental and stimulating risk. The aim of the research is to investigate the level of A-trait (in physically dangerous conditions and in new, unusual situations) and the level of R-TB (instrumental and stimulating risk) in athletes, and to verify to what extent A-trait and risk-taking behavior predict injury severity. Materials and methods: 154 senior martial arts athletes from grappling combat sports, striking combat sports and mixed martial artists (MMA) participated in the study. For assessing trait anxiety and risk-taking behavior, the Romanian adaptation of the Endler Multidimensional Anxiety Scales (EMAS), respectively the Romanian adaptation of the Makarowski's Stimulating and Instrumental Risk Questionnaire were used. Results: Using multivariate analysis of variance, significant differences between athletes (according to the sports disciplines practiced), in terms of A-trait and R-TB, were examined. Next, we checked the existing correlations between injury severity, A-trait and R-TB scores in athletes practicing striking combat sports, grappling combat sports and MMA. To verify whether there are significant differences in terms of trait anxiety, stimulating and instrumental risk between athletes who have suffered mild, moderate and/or severe injuries and athletes who have suffered only minor/mild injuries, t-Test for Independent Samples was used. Binomial logistic regression procedures were, also, performed, predicting athletes' likelihood of injury, based on R-TB and A-trait. Conclusion: A moderate or slightly below average level of anxiety in new, unusual situations and a higher level of instrumental risk are linked with a decreased likelihood of severe injuries in athletes. Martial arts athletes (in entire sample) who have suffered more severe injuries are more adrenaline-seeking in competition and use less rational thinking, taking more pleasure in just performing technical executions, regardless of the outcome.